Author Meets Readers: On Rein Raud's Being in Flux. Issue 3 (2nd September 2022) - Wirth, Jason M.; Liu, Jennifer; Raud, Rein
ABSTRACT: This is the first of an ongoing series of review essays in which the authors of significant new works of philosophy engage their readers. These inaugural two readings discuss Rein Raud's important new reassessment of contemporary ontology, Being in Flux: A Post-Anthropocentric Ontology of the Self . They consider its accomplishments, both on its own terms and with reference to its East Asian and South Asian precursors. Raud then offers a response.